Students’ Perceived Challenges of Attending a Flipped EFL Classroom in Viet Nam - Nguyen Huu Anh Vuong; Tan, Choon Keong; Lee, Kean Wah (2018)
Flipped classroom is gaining more and more popularity among educators and researchers all over the world; however, its implementation in Viet Nam is still in infancy. This small-scale research project attempts to investigate students’ perceived challenges when attending a flipped English grammar class. Qualitative research design was adopted to address the research question. The participants include 34 second year students majoring in the English language at a state university in Viet Nam. The instruments consist of an open-ended questionnaire and semi-structured interviews. Thematic analysis was employed to address the qualitative data. The findings highlight that Vietnamese students encounter several challenges when attending the flipped classroom including difficulty in self-regulated learning, heavy learning workload, lack of immediate support and lack of ICT resources. Accordingly, the present research has some pedagogical implications to help address those obstacles for successful implementation of this innovative teaching mode in the Vietnamese EFL context.